Optimalisasi Media Pembelajaran Dalam Menumbuhkan Minat Belajar Siswa - Aknes Wulandari; Puspita Indriani; Laras Wati (Lembaga Pengembangan Kinerja Dosen, 2025)
Advances in science and technology drive innovation in learning, especially through the optimization of learning media to foster students' interest in learning. This study aims to explore how the use of learning media can foster students' interest in learning at SMP Negeri 17 Batang Hari. The research approach is qualitative research with a case study approach, involving teachers and students as the main contributors. Information was collected through observation and in-depth interviews that focused on student engagement, material appeal, content clarity, learning motivation, digital interactivity, and changes in attitudes and values. The findings of this study indicate that learning media such as videos, images, animations, and digital applications can significantly increase student engagement and interest in learning. Visual aids enable students to understand abstract ideas in a more tangible way and facilitate the dissemination of content. Digital aids create an interactive and engaging learning environment that encourages students to be actively involved. Teachers also find these materials useful for clarifying exchanges, reducing words, and encouraging students to engage in structured reasoning. Learning Media not only improves academic achievement but also contributes to the emergence of values ​​such as collaboration, creativity, and digital ethics. This study concludes that optimizing learning media can produce a dynamic and relevant learning process, even though there are technical constraints in selecting learning tools that are tailored to student characteristics.